(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: In most literature regarding speech outcomes in children with repaired cleft lip and palate (CLP), exhibited resonance disorders despite having surgical repair. However, the types and severity of the resonance disorders vary from one individual to another. Thus, perceptual evaluation is important to determine the speech outcomes in individuals with repaired cleft lip and palate. Aim: The aim of this cross sectional study was to determine the types and severity of resonance disorders of children with repaired unilateral cleft lip and palate (UCLP) and describe the inter- and intra-rater reliability of perceptual evaluation of resonance disorders using GOS. SP.PASS’98. Four children with repaired UCLP in Hospital USM with ages ranging from 8 years old to 12 years old was included in this study. During data collection, history taking was first conducted, then participants’ speech sample was collected and lastly oral motor examination was conducted. Results: 50% of the speech sample was then duplicated for inter- and intraexaminer reliability investigations. Exact agreement and kappa values were used for reliability measures. Seventy five percent (75%) (3/4) participants exhibited hypernasality as the type of resonance disorder and 25% (1/4) participant had no evidence of hypernasality or any other types of resonance disorder. No other types of resonance disorders such as hyponasality, mixed resonance or cul-de-saq was noted in the participants. The severity of hypernasality ranged from mild to severe in the participants. Inter-rater reliability showed fair to almost perfect agreement and intra-rater reliability revealed almost perfect agreement. Conclusion: The results obtained from this study was more or less similar to our other studies conducted on the speech outcome of individuals with repaired UCLP. Although surgical intervention has been provided to these individuals, it is important that referrals be made to SLPs to evaluate their speech outcomes. This is to determine a proper management for the individual. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.282-289